EVALUATION OF THE LEFT VENTRICULAR GLOBAL LONGITUDINAL STRAIN IN PATIENTS WITH SEVERE AORTIC STENOSIS THAT UNDERGO SURGICAL AORTIC VALVE REPALCEMENT: A CASE REPORT - Zafirovska, Planinka; Ismail, Ljubica Georgievska; Matveeva, Niki; Mitrev, Zan (Journal of Morphological Sciences; Vol 1 No 2 (2018): JMS, 2018)
ABSTRACT Introduction and goal: Degenerative aortic stenosis is the most common valvular disease for which treatment of choice is stil surgery. Without the presence of symptoms, evaluation of systolic function of the left ventricle (LV) is crucial in surgical treatment decision making. Global longitudinal strain (GLS) is a valuable marker for subclinical systolic dysfunction delivering promising conditions for the right timing of the surgical aortic valve replacement (SAVR). Material and methods: We present a case of a 57-year old male with severe aortic stenosis. Detailed echocardiographic examination was performed including GLS of the LV with 2D speckle tracking before and after SAVR. Results: The ejection fraction before and after the surgical treatment was normal. GLS before the surgical treatment was -15, 1%, for 3-chamber GLS the value was -15,3%; for 4-ch it was  -14,2% and 2-ch counted -16%. After replacement of the aortic valve with mechanical prosthesis, the echocardiographic assessment done 4 months later showed improvement of the GLS values to -17,1% ( -18,5% for 3-ch, -15,0% for 4-ch and -17,1% for 2-ch).   Conclusion: Global longitudinal strain (GLS) of the LV is abnormal in patients with severe aortic stenosis. Surgical treatment of aortic stenosis improves GLS of the LV implicating improvement of the subclinical systolic dysfunction of the LV. Key words: aortic valvular stenosis, longitudinal strain, systolic function, echocardiography